2012
DOI: 10.1099/jmm.0.040758-0
|View full text |Cite
|
Sign up to set email alerts
|

Chelating agents exert distinct effects on biofilm formation in Staphylococcus aureus depending on strain background: role for clumping factor B

Abstract: Staphylococcus aureus is a leading cause of catheter infections, and biofilm formation plays a key role in the pathogenesis. Metal ion chelators inhibit bacterial biofilm formation and viability, making them attractive candidates as components in catheter lock solutions. The goal of this study was to characterize further the effect of chelators on biofilm formation. The effect of the calcium chelators ethylene glycol tetraacetic acid (EGTA) and trisodium citrate (TSC) on biofilm formation by 30 S. aureus strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 28 publications
(21 reference statements)
0
42
0
Order By: Relevance
“…Out of these, we found only two, TCH60 and ST38, with mutations leading to premature stop codons. Because we found in our earlier study (Abraham et al, 2012) that nearly 30 % of S. aureus isolates form strong biofilms in EGTA, and we confirmed in a number of these strains that biofilm formation in EGTA was ClfB-dependent, we hypothesize that additional genetic differences must lead to the observed phenotype in other strains. For example, clfB transcript levels could be higher in some strains or aur transcript levels could be lower.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Out of these, we found only two, TCH60 and ST38, with mutations leading to premature stop codons. Because we found in our earlier study (Abraham et al, 2012) that nearly 30 % of S. aureus isolates form strong biofilms in EGTA, and we confirmed in a number of these strains that biofilm formation in EGTA was ClfB-dependent, we hypothesize that additional genetic differences must lead to the observed phenotype in other strains. For example, clfB transcript levels could be higher in some strains or aur transcript levels could be lower.…”
Section: Discussionmentioning
confidence: 66%
“…We found previously (Abraham et al, 2012) that a subset of S. aureus strains produce strong biofilms in the presence of the chelating agents EGTA and trisodium citrate. We also found that if we deleted clfB in these strains, the ability to produce a biofilm under chelating conditions was nearly completely abolished.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some metal ions play an important role in biofi lm formation, stimulating cell-cell adhesion and aggregation (Abraham et al 2012 ), and the effect of metal ion chelation upon biofi lm formation has been investigated as a strategy to combat biofi lms. Ethylenediaminetetraacetic acid (EDTA) was shown to disperse P. aeruginosa biofi lms and result in 1,000-fold enhanced killing by gentamicin (Banin et al 2006 ), while a combination of EDTA and minocycline effectively reduced in vitro and ex vivo staphylococcal catheter colonization (Raad et al 2003 ).…”
Section: Metal Ions and Chelationmentioning
confidence: 99%
“…However, more recently, bacterial surface proteins involved in cell-cell interactions have also been identified [6]. S. aureus and S. epidermidis surface proteins that have been implicated in biofilm formation include SasC [7], SesC and Embp [8], fibronectin-binding proteins (FnBPs) [9][10][11], the fibrinogen-binding protein ClfB [12], SasG and Aap [13,14] and the recently discovered Sbp which influences both polysaccharide and protein-dependent biofilm formation in S. epidermidis [15]. The balance between PNAG/PIAdependent and protein-dependent biofilm formation affects biofilm morphology and this balance can differ between S. aureus and S. epidermidis; clinical and non-clinical isolates and under different environmental conditions [9,[16][17][18].…”
Section: Introductionmentioning
confidence: 98%